G206(P) Improving trainees' confidence in managing outpatients: Complete clinic management. (27th April 2016) - Mitchell, R; Fertleman, C
Abstract : Aims: Trainees must be competent and confident at handling both the clinical and managerial aspects of outpatient work. This is increasingly important as paediatricians aim to reduce inpatient stays with new directives to ensure that specific patient groups are seen within certain time frames in outpatients. Clinic experience for trainees is often trumped by acute service needs, and whilst the clinical aspects of outpatient work can often be covered by exposure to patients on a day to day basis, we recognised that trainees do not get exposure to the managerial aspects of outpatients. We therefore decided to plan a relevant study day. We envisaged educating senior trainees in the managerial aspects of outpatients, hoping that this would improve their experience of clinics and to inform the consultant workforce of the future. Methods: We used multi-modality feedback to inform the content of a clinic management study day. We ran 'Complete Clinic Management' twice in 2015. We collected pre course and post course (immediate and delayed [4 months]) questionnaires, assessing trainees' confidence in both the clinical and managerial aspects of outpatients. Results: 48 senior trainees attended this course and overall felt more confident in outpatients immediately after the course (p= <0.05). In particular they felt more confident planning a clinic, assessing referrals, and understanding the financial aspects of managing outpatients (p= <0.05). Four months on, trainees gave examples about how their learning had altered their practice. Specific examples included a trainee feeling "empowered" to make the most of clinic time, trainees taking active roles in triaging referrals, and trainees getting involved in quality improvement work around some of the managerial and financial of outpatients locally. Conclusions: Complete Clinic Management was very successful, with trainees feeling significantly more confident in the managerial aspects of outpatients after attending. This has shaped the way that trainees approached their clinic time going forward. Providing management teaching for senior trainees is key in ensuring they make the most of their clinical time, and will also help to shape our consultant workforce in the future.